Importance of the Habenula for Avoidance Learning Including Contextual Cues in the Human Brain: A Preliminary fMRI Study - Yoshino, Atsuo; Okamoto, Yasumasa; Sumiya, Yuki; Okada, Go; Takamura, Masahiro; Ichikawa, Naho; Nakano, Takashi; Shibasaki, Chiyo; Aizawa, Hidenori; Yamawaki, Yosuke; Kawakami, Kyoko; Yokoyama, Satoshi; et al. (Frontiers in Human Neuroscience, 2020)
Human habenula studies are gradually advancing, primarily through use of functional magnetic resonance imaging (fMRI) analysis of passive (Pavlovian) conditioning tasks as well as probabilistic reinforcement learning task. However, no studies have particularly targeted aversive prediction errors, despite the essential importance for the habenula in the field. Complicated learned strategies including contextual contents are involved in making aversive prediction errors during the learning process. Therefore, we examined habenula activation during a contextual learning task. We performed fMRI on a group of 19 healthy controls. We assessed the manually traced habenula during negative outcomes during the contextual learning task. The Beck Depression Inventory-Second Edition (BDI-II), the State-Trait-Anxiety Inventory (STAI), and the Temperament and Character Inventory (TCI) were also administered. The bilateral habenula was activated during aversive outcomes and the activation was associated with aversive prediction errors. There was also a positive correlation between TCI reward dependence scores and habenula activation. Furthermore, dynamic causal modeling (DCM) analyses demonstrated bilateral habenula to bilateral hippocampus connections during the presentation of contextual stimuli. These findings serve to highlight the neural mechanisms that may be relevant to understanding the broader relationship between the habenula and learning processes.